2022
DOI: 10.1002/bab.2364
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the key genes in the biosynthetic pathways of lipid A and peptidoglycan in Escherichia coli

Abstract: Gram-negative bacterium Escherichia coli has a tripartite cell envelope with a cytoplasmic membrane, a peptidoglycan layer, and an asymmetric outer membrane containing lipopolysaccharide in its outer leaflet. The biogenesis of peptidoglycan and lipopolysaccharide shares the same substrate UDP-GlcNAc. From UDP-GlcNAc, MurA catalyzes the first reaction for peptidoglycan biosynthesis, while LpxA catalyzes the first reaction for lipopolysaccharide biosynthesis. This study demonstrates that murA overexpression in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another important component of cell walls in gram-negative bacteria is lipopolysaccharide. The lpxA, lpxB, and lpxK genes, which are related to its synthesis process, were down-regulated by 2.05 fold, 2.13 fold, and 2.07 fold, respectively, thus directly affecting the synthesis of lipopolysaccharide (Figure 4a) [18]. The above results indicated that CPF-Fe could inhibit the synthesis of gram-negative bacterial cell walls.…”
Section: Cpf-fe Destroyed the Cell Membrane/wallmentioning
confidence: 87%
“…Another important component of cell walls in gram-negative bacteria is lipopolysaccharide. The lpxA, lpxB, and lpxK genes, which are related to its synthesis process, were down-regulated by 2.05 fold, 2.13 fold, and 2.07 fold, respectively, thus directly affecting the synthesis of lipopolysaccharide (Figure 4a) [18]. The above results indicated that CPF-Fe could inhibit the synthesis of gram-negative bacterial cell walls.…”
Section: Cpf-fe Destroyed the Cell Membrane/wallmentioning
confidence: 87%